Islamic Legal Analysis of Obligation for Swab Tests as a Requirement for Marriage in the Era of Covid-19 Pandemic in Indonesia - Shofiatul Jannah; Mohammad Afifulloh (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
The Covid-19 pandemic gives many impacts on various aspects, including marriage service requirement. During the pandemic, it is required to comply with government policies, namely submitting negative Covid-19 Swab test results for prospective brides, witnesses, and marriage guardians. Due to the high spending for taking the test, some prefer to unregister the marriage and delay the schedule. This research is a literature study with a normative type. The data was obtained qualitatively through observation and analysis of the policy of the Ministry of Religious Affair, its impact on Indonesian society, and how Islamic law percieves the policy. The results show that the policy of the Ministry of Religious Affair number: P-001/DJ.III/Hk.007/07/2021 aimed to cope with the spread of Covid-19 virus which is increasingly rampant. Meanwhile, according to the Islamic law, it is a temporary requirement formulated to prevent harm and therefore, it is not a part of marriage pillar. Islamic law furthermore puts it as an effort to maintain the soul's safety (hifdun al-nafs). (Pandemi Covid-19 memberi dampak pada berbagai macam aspek kehidupan, termasuk persyaratan layanan pernikahan. Selama pandemi, pasangan yang akan menikah, saksi, dan walinya diwajibkan menyerahkan hasil negatif test Swab sesuai kebijakan pemerintah. Karena mahalnya biaya test tersebut, ada beberapa pasangan yang memilih pernikahan sirri atau menunda pernikahannya. Penelitian ini adalah penelitian pustaka yang berjenis normatif. Data-data di dalamnya diperoleh secara melalui pengamatan dan analisis terhadap kebijakan Kementerian Agama nomor P-001/DJ.III/Hk.007/07/2021 yang bertujuan menanggulangi penyebaran virus Covid-19 yang sempat menggila. Sementara itu menurut hukum Islam, persyaratan tersebut sifatnya sementara dan bertujuan untuk mencegah munculnya hal-hal yang tidak diinginkan sehingga bukan meupakan rukun nikah. Hukum Islam melihat kebijakan tersebut sebagai salah satu upaya untuk menjaga keselamatan jiwa.)